The Impact of Centralized Personnel Functions in State Governments - Wortman, Max S.; Meyer, Gavin (Academy of Management Journal, 1969)
The authors, using a questionnaire, get the views of 46 of our state personnel administrators on the interrelationships of factors such as centralization, urbanization, merit rating and unionization.